2011
DOI: 10.1039/c0cc05229a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilically stabilized gold nanostars as SERS labels for tissue imaging of the tumor suppressor p63 by immuno-SERS microscopy

Abstract: A biocompatible, seed-mediated synthesis of monodisperse ~60 nm gold nanostars, followed by hydrophilic stabilization with ethylene glycol-modified Raman reporter molecules, is presented. Their application as SERS labels for imaging of the tumor suppressor p63 in prostate biopsies by immuno-SERS microscopy is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
119
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 19 publications
2
119
1
3
Order By: Relevance
“…Immuno-labeling SERS has was demonstrated for detecting antigens in tissues [334], and was continued using Au nanostar SERS labels for imaging a tumor suppressor in prostate biopsies [335]. Other ex vivo studies of human tissue include breast adenocarcinoma diagnosis using Au/SiO2 nanoclouds [336], colorectal cancer detection by SERS-based blood serum screening [337], measurement of normal and cancerous nasopharyngeal tissue [338], and colon carcinoma vs normal tissue [339].…”
Section: Applicationsmentioning
confidence: 99%
“…Immuno-labeling SERS has was demonstrated for detecting antigens in tissues [334], and was continued using Au nanostar SERS labels for imaging a tumor suppressor in prostate biopsies [335]. Other ex vivo studies of human tissue include breast adenocarcinoma diagnosis using Au/SiO2 nanoclouds [336], colorectal cancer detection by SERS-based blood serum screening [337], measurement of normal and cancerous nasopharyngeal tissue [338], and colon carcinoma vs normal tissue [339].…”
Section: Applicationsmentioning
confidence: 99%
“…A stoichiometric ratio of Ra 1 : Ra 2 ¼ 100 : 1 was chosen to ensure the steric accessibility of the carboxyl groups in the densely packed SAM. 19,20,39 The addition of DTNB-MEG-OH (Ra 1 ) and DTNB-TEG-CO 2 H (Ra 2 ) to the metal colloid leads to a hydrophilically stabilized self-assembled monolayer comprising two different terminal spacer units (dual spacer-SAM, cf. Fig.…”
Section: Characterization Of Antibody-sers Label Conjugatesmentioning
confidence: 99%
“…1B and Scheme 1A). [17][18][19][20] The benets of using MEG-OH and TEG-CO 2 H as hydrophilic spacers attached to aromatic Raman labels include the increased stability of the SERS labels due to the EG termini and the controllable bioconjugation via the MEG-OH/TEG-CO 2 H stoichiometry, together with the advantages of a SAM (maximum surface coverage with Raman reporters, uniform molecular orientation, and minimal coadsorption of other molecules from the surrounding onto the metal surface). SERS immunoassays have been reported for the detection of cell surface antigens, 21 immunoglobulin G (IgG), 8,13 protein A,…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies directed against the protein p63 were conjugated to SERS labels with this protocol and were employed in immunohistochemistry. 55,94,121 b Polymer-encapsulated SERS nanoprobes. Polymerencapsulated SERS labels oen provide terminal functional groups from the polymer shell.…”
Section: Conjugation Of Ligands To Protected Sers Labelsmentioning
confidence: 99%
“…54 To avoid the use of CTAB and toxic DMF, Schütz et al have developed a biocompatible synthesis route towards monodisperse gold nanostars ( Fig. 4F) in water, with sodium citrate and hydroquinone as reducing/capping agents; 55 it was demonstrated that the as-prepared gold nanostars can be used as efficient SERS labels for tissue imaging.…”
mentioning
confidence: 99%